On the measurement of piezoelectric d33 coefficient of soft thin films under weak mechanical loads: A rapid and affordable method - Gaia de Marzo; Luca Fachechi; Valentina Antonaci; Vincenzo Mariano Mastronardi; Luigi Portaluri; Maria Teresa Todaro; Luciana Algieri; Antonio Qualtieri; Francesco Rizzi; Michele Scaraggi; Massimo De Vittorio (Materials & Design)
Thanks to their intrinsic flexibility, energy efficiency and high portability, soft piezoelectric thin films represent the most effective technological approach for wearable devices to monitor health conditions. In order to improve effectiveness and applicability, more and more innovative and high-performing soft piezoelectric materials are being developed and benchmarked through their piezoelectric d33 coefficient. However, most existing methods to measure the d33 were developed for ceramic or bulk materials and cannot be applied to soft materials because high force/pressure can deform and damage the material structure. This work introduces a simple, effective, and fast method to accurately measure the d33 of soft and thin piezoelectric films by applying weak sinusoidal forces to avoid any damage to the sample, and simultaneously measuring the charges produced by the direct piezoelectric effect. The approach is versatile as it can be used for different types of materials and sizes of the active area. This method represents an effective solution to speed up the process of material optimization, paving the way for the rapid development of novel wearable piezoelectric devices.